The Church in Densuş Between the Sacred and the Profane - Petruța Iulia Luchian (Anastasis: Research in Medieval Culture and Art)
Temple of Zamolxe, pagan Roman temple of the god Mars, mausoleum of Trajan’s best friend, the general Longinus Maximus, church built by the Goths in the 4th century, “divine work stolen by nocturnal genies”1, the first church in Haţeg and perhaps in the entire country, “unparalleled in all Romania”2, foundation of Litovoi, a church similar to Sân-Nicoara in Curtea de Argeş, or a church with a triptych as valuable as that of the famous Rubliov, “St. Nicholas” Church is an Orthodox place of worship in Densuș, Hunedoara county; one of the oldest churches in Romania, apparently dating from the 12th-13th centuries, built on the ruins of a building from the 4th century AD, it has a square plan, with the nave pierced by a tower, resting on a vault and equipped with a deep semicircular apse; the entire construction is covered with stone slabs, and most of its material (river boulders, marble slabs with Latin inscriptions, capitals, tombstones, sewer pipes) comes from Ulpia Traiana Sarmizegetusa, the capital of Roman Dacia (located nearby); the mural painting of the monument dates from the 15th century. The Densuş church, like any unclassifiable and imprecisely dated monument, becomes a mitigating argument for any demonstration about the descendants of the Dacians, the beginning of Christianity, the paths of migratory peoples, the existence of Romanians or about the creative and universal genius of our people.